Power Line Communications: An Overview - Part I - Yousuf, M.S. (2007)
We give an overview of the power line communications (PLC) technology, its importance, its standards and an overview of the HomePlug standards associated with it. This is done is two parts due to publication constraints. In this part, we will concentrate on the PLC applications and the technical issues regarding it. We will also see the layers and methods that are needed to make it work.